Spontaneous Dissemination in Neighboring Provinces of DKA Prevention Campaign Successfully Launched in Nineties in Parma’s Province - Cangelosi, Antonina Marta; Bonacini, Ilaria; Serra, Roberta Pia; Di Mauro, Dora; Iovane, Brunella; Fainardi, Valentina; Mastrorilli, Carla; Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2017)
Aim: to investigate how much effectiveness of the historical campaign of DKA prevention at T1D diagnosis has survived in Parma’s province where this was launched in Nineties, and how much it has spontaneously spread in the neighboring provinces. Method: children aged 6-14 years with newly diagnosed TID coming from province of Parma (Group 1) and from two other nearby provinces (Group 2)  were investigated. Clinical and laboratory data were retrospectively collected from medical files of each patient and included age, gender, capillary pH, serum bicarbonate, 3-beta-hydroxybutyrate (3HB), glycated hemoglobin (HbA1c) at the time of admittance from 1st January 2012 and 31 December 2016. Results:no DKA condition was globally found in 25/36 patients (69.4%): 16/17  and 9/19 patients  belonged to Group 1 and 2 respectively (p=0.002). Mild or moderate DKA was reported in 5.9% patients of Group 1 and in 47.31%  (p=0.005) patients from Group 2. Severe DKA was observed in only 1 child from Group 2. Normal 3-beta-hydroxybutyrate (3HB) serum levels was reported in the 25 patients without DKA at diabetes diagnosis. Duration of hyperglycemia-related symptoms before overt T1D diagnosis was shorter (4.6±2.5 days) in patients with 3HB levels